Approach Integration Design Sprints to Design Thinking in Learning Management System Sakattaku - Nida, Siti Nabilah; El Akbar, R Reza; Rahmatulloh, Alam (Universitas Muhammadiyah Surakarta, 2024)
The Ministry of Education and Culture has introduced a new phase of its independent learning policy called the Movement Organization Program (POP). As a participant in POP, the Sakata Innovation Center Foundation offers a Saung Coding training program that combines hybrid learning methods, including utilizing the Sakattaku Learning Management System (LMS) platform. However, feedback from teachers and school principals indicates that 45% of the respondents (20 out of 45) faced difficulties and discomfort while using the LMS. The user interface (UI) and user experience (UX) are crucial in enhancing the system's functionality and overall user satisfaction. Hence, this research aims to analyze and develop a plan to implement improvements in the UI/UX of the sakattaku.com LMS. The study also involves testing the system and recommending design enhancements. By prioritizing UI and UX, the research combines the compatibility of Design Thinking and Design Sprint methodologies. The final findings indicate that 9 of 15 expert users completed the assigned scenario tasks successfully. The User Experience Questionnaire (UEQ), administered to a sample of 45 individuals, yielded positive impressions across all assessment aspects, with particular improvement noted in the clarity aspect, which transformed from a below-average rating to an excellent rating. Additionally, the novelty aspect exhibited the highest positive difference, with a value of 75.6%.